"Emergencia timonensis, " a new bacterium isolated from the stool of a healthy patient. (July 2016) - Bessis, S.; Ndongo, S.; Lagier, J.-C.; Fournier, P.-E.; Raoult, D.
Abstract: We present the essential characteristics of "Emergencia timonensis" strain SN18 (= CSUR P2260), a new member of the order Clostridiales that was isolated from the stool of healthy patient.